Artificial Intelligence and the Future of Online Marketing: Emerging Pathways and Consumer Experiences - Otieno, Amina K.; Mwakalukwa, Emmanuel J.; Wanjiru, Faith N. (Tecno Scientifica Publishing, 2025)
Online marketing has undergone a transformative evolution alongside the rise of social media and artificial intelligence (AI). With the increasing sophistication of algorithms that determine user engagement and content exposure, the intersection of AI and marketing presents new challenges and opportunities. This short communication outlines three progressive levels of AI integration in digital marketing: predictive modeling, virtual assistants, and ultra-personalized experiences. By illustrating how predictive analytics can optimize consumer targeting, virtual assistants can enhance user interaction, and AI-driven personalization can redefine customer journeys, this paper provides a conceptual roadmap for understanding the trajectory of AI-driven marketing. The discussion highlights potential ethical and privacy implications, emphasizing responsible deployment and equitable consumer engagement. The article concludes with reflections on future directions and the transformative potential of AI in shaping digital marketing strategies.